Dosing, efficacy and safety of lenvatinb in the real‐world treatment of hepatocellular carcinoma: Results from a Canadian database. Issue 3 (16th July 2022) - Pires Amaro, Carla; Allen, Michael J.; Knox, Jennifer J.; Tsang, Erica S.; Lim, Howard J.; Lee‐Ying, Richard M.; Chan, Kelvin W.; Qian, Jessica; Meyers, Brandon M.; Thawer, Alia; Al‐Saadi, Sulaiman M. S.; Hsu, Tina; et al.
Abstract: Background and Aims: A phase 3 trial showed lenvatinib to be effective and safe in the treatment of unresectable hepatocellular carcinoma (HCC), however, its performance in the real world and effect of dosing on survival are unclear. Methods: From July 2018 to June 2020, HCC patients treated with lenvatinib from 10 Canadian cancer centres were included. Overall survival (OS) and progression‐free survival (PFS) were retrospectively analysed and compared across first‐ and later lines use of lenvatinib. In patients receiving lenvatinib first‐line, OS between different mean dose intensities and starting doses were compared. Results: A total of 220 patients were included, of which 79% received lenvatinib as first‐line therapy. For first‐line versus later line treatment, median OS was 12.5 versus 11.8 months ( P  = .83) and median PFS was 7.6 versus 4.6 months ( P  = .27) respectively. Of patients receiving lenvatinib first‐line, 54% started at full dose according to their weight. Median OS for patients starting lenvatinib at full‐ and reduced‐dose was 12.3 and 15.8 months ( P  = .75) respectively. Median OS for patients with a mean dose intensity >66.7% compared ≤66.7% was 13.7 and 7.7 months ( P  = .01). In the multivariate analysis, dose intensity (>66.7 vs ≤66.7%) did not predict for OS [HR 0.70, 95% CI 0.42–1.18; P  = .18]. The most common side effects were fatigue (59%), hypertension (41%) and decreased appetite (25%). Conclusions: Lenvatinib appears to be effective in real‐world practice regardless of the line of therapy. Dose modifications at the start or during treatment did not appear to significantly affect survival. Abstract : Lenvatinib appears to be effective in real‐world practice regardless of the line of therapy. Dose modifications at the start or during treatment did not appear to significantly affect survival.